IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 PADA PEMBUATAN PERJANJIAN PERKAWINAN - Aryani, Nyoman Mas (Institut Hindu Dharma Negeri Denpasar, 2018)
Law Number 1 Year 1974 on Marriage, embraces the principle of separate property where except husband and wife determine otherwise by making a marriage agreement before or at the time of marriage is held. In the middle of 2015, Ike Farida, a lawyer who performs a mixed marriage, filed a petition for judicial review to the Constitutional Court because he felt his constitutional rights were injured by the enactment of Law Number 5 of 1960 on Basic Agrarian Law, namely Article 21 paragraph (1), (3), Article 36 paragraph (1); and Article 29 paragraph (1), (3), (4) and Article 35 paragraph (1) of the Marriage Law. The Constitutional Court through Decision Number 69 / PUU-XIII / 2015, in particular on the verdict stating: “At the time or before the marriage takes place or during the marriage bond, the two parties to mutual consent may submit a written agreement authorized by the marriage registry officer, after which the contents also apply to the third party caught “. This poses a problem where it will be difficult to know the existence of a third party related to the making of a marriage agreement. The conclusion is that the Constitutional Court Decision does not regulate the legal consequences of marriage agreement after marriage to the status of property but implicitly regulate the legal effect on a third party